PEMBINAAN KEWIRAUSAHAAN PRODUK PEMULA SELAI PISANG DI DESA GIRIWARINGIN, KECAMATAN MALEBER KABUPATEN KUNINGAN JAWA BARAT - Komarudin Komarudin; Ugeng Budi Haryoko; Mulyadi Mulyadi; Sutrisno Sutrisno; Muliahadi Tumanggor (LPPM Universitas Pamulang, 2020)
The booming production of bananas in Giriwaringin Village, Maleber District, Kuningan Regency gave an idea for some residents to use bananas. Lots of bananas, processed into delicious snacks that are sale of bananas. However, the sale of bananas produced still does not have good quality so they cannot compete in the market. This service is titled Development of Banana Jam Starter Entrepreneurship in Giriwaringin Village, Maleber District Kuningan Regency West Java The purpose of this community service is to Provide Entrepreneurship Development for Banana Jam Starter Products in GiriwaringinVillage, Maleber District, Kuningan, West Java Regency. The method of implementing this service is carried out in several activities, namely by involving many parties other than the residents of the village of Giriwaringin also involving parties from the subdistrict starting from the sub-district, and sub-district staff in the Maleber sub-district, Kuningan regency, West Java Province. The conclusion of community service (PKM) is that in general community service activities can be carried out well and received a warm welcome and support from the village of Giriwaringin in terms of place, infrastructure and accommodation facilities, as well as enthusiastic residents of Giriwaringinvillage to produce banana jam.Keywords: Entrepreneurship Development, Banana Jam Products